INVESTIGATION OF THE INFLUENCE OF RARE-EARTH METAL IMPURITIES ON THE CONDUCTIVITY OF LITHIUM-IRON SPINEL - Vakalyuk, Andrii; Vakalyuk, Vasyl (SWorld-Ger Conference proceedings, 2025)
The temperature-frequency dependences of the electrical characteristics of Li2Fe2,5-xMexO4 (Ме=La;Y, x=0;0.01;0.03;0.05) spinels synthesized by the «sol-gel» auto-combustion technology were obtained by the method of impedance spectroscopy in the tem